Pembentukan Karakter melalui Pembelajaran Ilmu Pengetahuan Sosial (IPS) - Rintati Megawati; Tutuk Ningsih (Institut Agama Islam Negeri Purwokerto, 2020)
The rapid development of communication and information technology that has been wrapped up in a global order of life has a complex impact on all groups, including the younger generation. In addition to the positive impact that has emerged, namely with the expansion of knowledge, the negative impact in the form of degradation of moral values and kindness among the young generation of Indonesia is starting to fade and even almost lost by this current wave. For this reason, alternative problem solving is needed so as not to dissolve in moral decline. One of them is through Social Sciences (IPS) education by giving its role to shape the nation's character. This paper aims to examine the formation of character through social studies learning. This study uses a qualitative-descriptive method to explore the values and character of education in Social Sciences (IPS) subjects with the researcher as the main instrument. Field findings show that the curriculum, materials, teachers and teaching and learning processes have an important role in the formation of students' character through social studies learning that is structured and designed to introduce and develop knowledge, understanding, and the ability to be sensitive and sympathetic to the environment with the principle of meaningful, integrated, challenging, active, and value-based.